Comparison of Natural Radioactivity of Commonly Used Fertilizer Materials in Egypt and Japan - Nabil M. Hassan; Byung-Uck Chang; Shinji Tokonami (Journal of Chemistry)
Specific activities of 238U, 232Th, and 40K in the environment have been redistributed by the use of fertilizers in agriculture so their concentrations in fertilizer materials should be measured to identify the safe utilization of fertilizers. In the present work, the specific activities of these radionuclides in five commonly used fertilizers in Egypt and five fertilizers used in Japan were measured by HPGe and γ-ray spectrometry. The average values of 238U, 232Th, and 40K in Japanese fertilizers were less than their values in Egyptian fertilizers but both had some samples with specific activities greater than the recommended limiting values. The radiological hazards of radium equivalent activity (Raeq), external (Hex) and internal (Hin) indexes, alpha and gamma indexes, and annual effective dose, due to the presence of these radionuclides, were calculated and compared with each other.